2021
DOI: 10.3389/fchem.2021.688108
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Systems for Hedgehog Inhibitors in the Treatment of SHH-Medulloblastoma

Abstract: Medulloblastoma (MB) is a highly aggressive pediatric tumor of the cerebellum. Hyperactivation of the Hedgehog (HH) pathway is observed in about 30% of all MB diagnoses, thereby bringing out its pharmacological blockade as a promising therapeutic strategy for the clinical management of this malignancy. Two main classes of HH inhibitors have been developed: upstream antagonists of Smoothened (SMO) receptor and downstream inhibitors of GLI transcription factors. Unfortunately, the poor pharmacological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…However, the shallow understanding of potential targets involved in the immunotype transformation from “cold” to “hot” has limited the development of precise combination treatment. The predictive biomarker identified in this study was based on the Hh signaling, recognized as a canonical oncogenic signaling and a therapeutic target 72,73 . Otsuka et al reported that tumor regression induced by Hh signaling inhibitor was accompanied by recruitment of cytotoxic T cells into the TME in BCC, 21 indicating the great potential of Hh signaling as a critical target in combination treatments.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the shallow understanding of potential targets involved in the immunotype transformation from “cold” to “hot” has limited the development of precise combination treatment. The predictive biomarker identified in this study was based on the Hh signaling, recognized as a canonical oncogenic signaling and a therapeutic target 72,73 . Otsuka et al reported that tumor regression induced by Hh signaling inhibitor was accompanied by recruitment of cytotoxic T cells into the TME in BCC, 21 indicating the great potential of Hh signaling as a critical target in combination treatments.…”
Section: Discussionmentioning
confidence: 87%
“…The predictive biomarker identified in this study was based on the Hh signaling, recognized as a canonical oncogenic signaling and a therapeutic target. 72 , 73 Otsuka et al reported that tumor regression induced by Hh signaling inhibitor was accompanied by recruitment of cytotoxic T cells into the TME in BCC, 21 indicating the great potential of Hh signaling as a critical target in combination treatments. Encouragingly, three clinical trials comparing the treatment efficiency between the mono ICI group or the combined group (ICI plus Hh inhibitors) in metastatic BCC patients will provide evidence of whether combination treatments serve as a better strategy than mono ICI strategy in BCC (NCT03521830; NCT03132636; NCT02690948).…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests better stability of the PTX PLGA/CD NPs as zeta potential with a higher negative magnitude value representing the nanoparticle's stability. It can be attributed to the presence of CD that is associated with improved stability of nanoparticles 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Medulloblastoma (MB) is a highly malignant neuroepithelial tumor of the central nervous system and is a common solid tumor in children ( Li M. et al, 2021 ; Wen and Hadden, 2021 ), particularly those under 10 years of age ( Hammoud et al, 2020 ; Danilenko et al, 2021 ). MB is difficult to treat because of its rapid growth, incomplete surgical excision, and tendency to disseminate with the cerebrospinal fluid ( Caimano et al, 2021 ). The current 5-year survival rate for MB treated with a combination of surgery, radiotherapy, and chemotherapy is 65%.…”
Section: Roles and Significance Of Circrnas In Pediatric Malignant Solid Tumorsmentioning
confidence: 99%